Revisiting Triple Helix Collaboration for Rural Empowerment through Appropriate Technology Village Cas - Rahayu, Sri; Hos, Jamaluddin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Rural development increasingly requires collaborative and context-sensitive approaches to transform local economic potential into sustainable community empowerment. However, limited attention has been given to how triple helix collaboration operates in village-level practices, particularly when linked to appropriate technology. This study examines the enactment of triple helix collaboration in rural community empowerment through appropriate technology in Tetehaka Village, Konawe Regency, Indonesia. A qualitative case study approach was employed, with data collected through in-depth interviews, observation, and documentation involving five purposively selected informants representing key stakeholders. Data were analyzed using an interactive process of reduction, display, and conclusion drawing. The findings indicate that although the core actors of the triple helix are present, their interaction remains fragmented, program-based, and insufficiently institutionalized. Appropriate technology has supported productive activities by improving efficiency and enabling basic digital practices; however, its impact is constrained by limited technological capacity, weak mentoring continuity, and insufficient coordination. The study highlights that sustainable rural empowerment depends not only on technology availability or actor presence but on the quality of collaboration, role alignment, and continuity of institutional support. This study contributes by extending triple helix theory into a rural village context and repositioning appropriate technology as an empowerment-oriented socio-technical instrument. It also proposes a context-sensitive collaboration model emphasizing structured coordination and continuous facilitation.